2016
DOI: 10.1155/2016/5276130
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antioxidants and Natural Products in Inflammation

Abstract: Inflammation is a comprehensive array of physiological response to a foreign organism, including human pathogens, dust particles, and viruses. Inflammations are mainly divided into acute and chronic inflammation depending on various inflammatory processes and cellular mechanisms. Recent investigations have clarified that inflammation is a major factor for the progression of various chronic diseases/disorders, including diabetes, cancer, cardiovascular diseases, eye disorders, arthritis, obesity, autoimmune dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
535
1
23

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 748 publications
(563 citation statements)
references
References 92 publications
(110 reference statements)
4
535
1
23
Order By: Relevance
“…Inflammation is a process associated with the imbalance of reactive oxygen species/reactive nitrogen species (ROS/RNS) and cellular antioxidants causing oxidative stress and oxidative damage of cellular components (Arulselvan et al, ) in diverse cell types. In addition, many evidences have pointed out that ROS act as a signaling molecule responsible to the gathering of numerous pro‐inflammatory cytokines (e.g., IL‐1β, IL‐6, and TNF‐α) and inducible enzymes involved in free‐radical generation (e.g., iNOS and COX‐2) (Blaser, Dostert, Mak, & Brenner, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is a process associated with the imbalance of reactive oxygen species/reactive nitrogen species (ROS/RNS) and cellular antioxidants causing oxidative stress and oxidative damage of cellular components (Arulselvan et al, ) in diverse cell types. In addition, many evidences have pointed out that ROS act as a signaling molecule responsible to the gathering of numerous pro‐inflammatory cytokines (e.g., IL‐1β, IL‐6, and TNF‐α) and inducible enzymes involved in free‐radical generation (e.g., iNOS and COX‐2) (Blaser, Dostert, Mak, & Brenner, ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-mutagenicity possibly associated with rosmarinic acid was present in both in PSE and PSME. Vattem et al (2006) demonstrated that the anti-mutagenic properties of rosmarinic acid in S. typhimurium system occurred through the protection of DNA from oxidative damage, by altering the cellular Inflammation is a process associated with the imbalance of reactive oxygen species/reactive nitrogen species (ROS/RNS) and cellular antioxidants causing oxidative stress and oxidative damage of cellular components (Arulselvan et al, 2016) in diverse cell types. In addition, many evidences have pointed out that ROS act as a signaling molecule responsible to the gathering of numerous pro-inflammatory cytokines (e.g., IL-1b, IL-6, and TNF-a) and inducible enzymes involved in freeradical generation (e.g., iNOS and COX-2) (Blaser, Dostert, Mak, & Brenner, 2016).…”
Section: Effect Of Pse and Psme On Inos And Cox-2 Mrna Expressionmentioning
confidence: 99%
“…A recent investigation suggested that there is an inverse relationship between dietary consumption of antioxidant-rich foods and prevalence of human illness (Arulselvan et al ., 2016). Therefore, in our opinion, incorporation of antioxidant – anti-inflammatory natural product compounds – either in the daily diet or as supplemental medicine, can be a promising and safe solution to solve human health issues, in particular chronic disorders, once their chemical properties are defined and pharmacological effects are elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Free from harmful side effects, adequate intake of natural AOC from foodstuff -mainly flavonoids and other phenolic compounds -was identified as a cheap and suitable means to counter both acute and chronic inflammations and prevent -and sometimes help treatingconsequent acute and chronic illnesses such as neurodegenerative diseases, cancer, diabetes, rheumatoid arthritis, inflammatory bowel disease and cardiovascular diseases (Arulselvan et al, 2016;Pérez-Cano and Castell, 2016;Vezza et al, 2016).…”
Section: Healthier Diets Mattermentioning
confidence: 99%